Vascular mechanism of axonal degeneration in peripheral nerves in hemiplegic sides after cerebral hemorrhage: An experimental study - Gundogdu, Cemal; Aydin, Memet Dumlu; Kotan, Dilcan; Aydin, Nazan; Bayram, Ednan; Ulvi, Hızır; Aygul, Recep (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Background Though retrograde neuronal death and vascular insufficiency have been well established in plegics following intracerebral hemorrhage, the effects of plegia on arterial nervorums of peripheral nerves have not been reported. In this study, the histopathological effects of the intracerebral hemorrhage on the dorsal root ganglions and sciatic nerves via affecting the arterial nervorums were investigated.Methods This study was conducted on 13 male hybrid rabbits. Three animals were taken as control group and did not undergo surgery. The remaining 10 subjects were anesthetized and were injected with 0.50 ml of autologous blood into their right sensory-motor region. All rabbits were followed-up for two months and then sacrificed. Endothelial cell numbers and volume values were estimated a three dimensionally created standardized arterial nervorums model of lumbar 3. Neuron numbers of dorsal root ganglions, and axon numbers in the lumbar 3 nerve root and volume values of arterial nervorums were examined histopathologically. The results were analyzed by using a Mann-Whitney-U test.Results Left hemiplegia developed in 8 animals. On the hemiplegic side, degenerative vascular changes and volume reduction in the arterial nervorums of the sciatic nerves, neuronal injury in the dorsal root ganglions, and axonal injury in the lumbar 3 were detected. Statistical analyses showed a significant correlation between the normal or nonplegic sides and plegic sides in terms of the neurodegeneration in the dorsal root ganglions (p < 0.005), axonal degeneration in the lumbar 3 nerve roots (p < 0.005), endothelial cell degeneration in the arterial nervorums (p < 0.001), and volume reduction in the arterial nervorums (p < 0.001).Conclusion Intracerebral hemorrhage resulted in neurodegeneration in the dorsal root ganglion and axonolysis in the sciatic nerves, endothelial injury, and volume reduction of the arterial nervorums in the sciatic nerves. The interruption of the neural network connection in the walls of the arterial nervorums in the sciatic nerves may be responsible for circulation disorders of the arterial nervorums, and arterial nervorums degeneration could result in sciatic nerves injury.